Development of a Conceptual Islamic Cyber-Ethical Model (ICEM) for Cybersecurity Professionals Based on Digital Islamic Education Values - Asruddin; Aulia, Muhammad Immawan; Oman Fathurohman SW (Al-Mau’izhoh: Jurnal Pendidikan Agama Islam, 2025)
Cybersecurity threats have become increasingly complex, requiring not only advanced technical competencies but also strong ethical foundations to guide responsible digital behavior. Current cybersecurity education often emphasizes technical skills but still lacks a comprehensive moral framework that integrates spiritual and ethical reasoning. This conceptual study develops the Islamic Cyber-Ethical Model (ICEM), a normative ethical framework derived from Islamic ethical principles and integrated into the paradigm of Digital Islamic Education. Using a library research method, this study synthesizes key Islamic ethical values amanah (trust), maslahah (public benefit), adab al-‘ilm (ethics of knowledge), anti-fasad (prevention of harm), and moral responsibility with global cybersecurity ethics principles such as confidentiality, responsible disclosure, risk minimization, and prevention of misuse. The resulting model consists of five components: Niyyah Checkpoint, Amanah Assessment, Maslahah Justification, Anti-Fasad Filter, and the Responsible Disclosure Protocol. ICEM provides a structured ethical reference for decision-making in cybersecurity practices, vulnerability handling, and digital responsibility. This model contributes theoretically to Islamic cyber ethics and offers a conceptual foundation for future empirical validation, curriculum development, and training programs for cybersecurity professionals.